AKTA PENGAKUAN HUTANG YANG DISERTAI DENGAN AKTA KUASA MENJUAL YANG MEMUAT KLAUSUL PEMBERIAN HAK KEPADA KREDITUR UNTUK MENENTUKAN HARGA DAN SYARAT PENJUALAN OBYEK JAMINAN - Johanes Dipa Widjaja (Maleo Law Journal, 2020)
The purpose of this study is to find out how the legal consequences of the deed of debt recognition accompanied by the power of attorney for sell which contains a clause granting the right to the creditor to determine the price and conditions of sale of the collateral object. This research was conducted using a statuttory approach and a conceptual approach (conceptual approach). Bosed on the ressults of this resiearch and discusion, it can be concludied that the deed of recognition of debt accompanied by a deed of selling power which contains a clause granting the right to the creditor to determine the price and terms of sale of the collateral object is considered to have violated the principle of good faith even if it was made before a competent official (in this case a notary ) because such a clause places the debtor in a very weak position that is vulnerable to arbitrary actions on the part of creditors such as selling the object of debt security at below market prices Keywords: Legal Deed of Debt Recognition, Power of Attorney For Sell, Debt Collateral.